Effect of a Nurse-Led Exercise Program on Depression in Elderly Patients with Diabetes: A Retrospective Study. - Li Peng; Ran Wei; Yi Lu (Actas Espanolas de Psiquiatria, 2024)
Background: Patients with diabetes often face psychological challenges, particularly depression. The coexistence of these two conditions can significantly impact both the mental and physical health of individuals. This study aims to investigate the effects of nurse-led exercise training on elderly patients diagnosed with type 2 diabetes mellitus and comorbid depression through experimental research. By selecting appropriate exercise programs for patients, the study seeks to identify effective strategies for improving both their physical health and depressive symptoms. Additionally, it aims to offer tailored exercise recommendations to enhance the overall well-being of these patients. Method: The observation group (n = 53) and the control group (n = 53) were selected based on the interventions documented in the patients' medical records, with eligible patients identified as research participants. The control group received standard medication, while the observation group engaged in intensive exercise training in addition to their standard treatment, dedicating 60-90 min per day to exercise. Prior to and following the intervention, blood glucose indices, levels of 5-hydroxytryptamine (5-HT) and norepinephrine (NE), self-rating depression scale (SDS), Self-Rating Anxiety Scale (SAS), Pittsburgh Sleep Quality Index (PSQI), and Generic Quality of Life Inventory (GQOLI-74) scores were assessed to evaluate the impact of the exercise training intervention. Result: Following the intervention, levels of fasting blood glucose (FBG), 2-h postprandial blood glucose (PBG), and Hemoglobin A1c (HbA1c) were reduced compared to pre-intervention levels, with the exercise group exhibiting lower levels than the control group (p < 0.05). Additionally, post-intervention, patients' levels of 5-HT and NE increased, with the exercise group demonstrating higher levels than the control group (p < 0.05). Moreover, post-intervention, SDS and SAS scores decreased, with more significant improvements observed in the observation group (p < 0.05). Furthermore, the intervention improved sleep quality and quality of life among patients in the exercise group compared to those in the control group (p < 0.05). Conclusion: Nurse-guided exercise training demonstrates a significant capacity to ameliorate glycemic indexes among patients with diabetes mellitus comorbid with depression. It not only diminishes depression and anxiety levels but also enhances the expression of 5-HT and NE. Furthermore, it effectively elevates patients' sleep quality and quality of life. These findings underscore the potential of nurse-led exercise interventions for clinical promotion and widespread application.